Age-Associated Variations in Vitamin D Levels among Diabetic and Non-Diabetic Men - Abdulhadi Mohamed Jumaa; Meqdam Atiyah Khalaf; Hassan Yashar Hassan (Disease and Health: Research Developments Vol. 8, 2025)
Background: The required quantities of exposure to sunlight differ from other seasons, as the majority of people suffer from reduced levels of vitamin D, especially during the winter season. The periods of exposure differ according to the seasons of the year, the place, terms of the skin exposed to the sun and the type of skin as well as the type of clothes, in the summer the best time For exposure is the middle of the morning or In the afternoon outside the peak of UV rays, while in the winter there are longer periods of exposure to the sun with the preference of the near time from the afternoon, it is important to establish a balance between the need for sunlight in order to produce what is appropriate for vitamin D and avoid the risk of a skin lesion with excessive exposure for the sun at the same time. Where it is estimated that the appropriate time to exposure is about 5 to 10 minutes on most of the summer days, and 30 minutes as a maximum during the winter days, and it is preferable that the arms, legs and face are the areas exposed to sunlight, and the period of exposure to the sun may vary depending on the type of skin, and it is useful to know that there is Light than UV rays through Regular transparent windows. Vitamin D is synthesized from precursors present at the surface of the epidermis and then undergo biotransformation which is achieved at the hepatocytes and finally by hydroxylation enzymes in the nephrons. Sunrays play a crucial role in the beginning of D vitamin formation processes, parathyroid hormone is an essential hormone secreted by parathyroid glands and plays a key role in the activation of D vitamin by renal alfa hydroxylase. Food sources of Vitamin D are also important for supplementation of the human body with some requirements. Aim: This study aimed to compare the concentration of vitamin D in diabetic patients, and non-diabetic men and its association with age. Patients and Methods: The current study started at the beginning of June 2018 and continued until the end of March 2019, at the outpatient unit in a special private hospital in Tikrit City - Iraq. Eighty men have been enrolled in the present study. Results: Eighty men participated in the present study, distributed as 40 non-diabetic subjects as controls and 40 diabetic patients. The mean and standard deviation of D vit. levels of non-insulin-dependent diabetes and normal physically fit men show there is a significant reduction of D vit. Measurements of the diabetic men patients suffering from T2DM, (13.58 ± 5.29) as compared with control subjects, (19.95 ±6.5). There is a significant decrease in vit. D measurements of T2DM young patients. In T2DM patients less than 18 years old have a significant reduction in vitamin D concentration, (13.41 ± 5.1), as compared with T2DM patients aged 18-40 years, (17.23 ± 7.3). Measurements of vit. D. During heat season and compared to cold months. The evaluation of Vit. D. During hot months shows a significant rise (26.4 ± 7.1) in comparison with winter status (13.65 ± 4.2). Conclusions: The present study concludes that, Vit. D levels show a highly important increment in hot months as compared with the winter season and there are significant reductions in the concentration of vitamin D in young age type 2 diabetic patients.